Daily exercise and its role in mitigating covid-19 severity in young adults: insights from reunion island - Dr. Claire B. Lefevre (International Journal of Medical Science and Public Health Research, 2025)
COVID-19 has significantly impacted global health, with individuals experiencing various degrees of severity and complications based on several factors, including age, pre-existing conditions, and lifestyle behaviors. Physical activity is one lifestyle factor that has been suggested to potentially offer protection against viral infections, including COVID-19. This study investigates the protective effect of daily physical activity in preventing or mitigating COVID-19 outcomes in a young adult population on Reunion Island, an overseas French territory. Data was collected via surveys distributed to university students and young adults between the ages of 18 and 30, to understand the correlation between physical activity levels and the severity of COVID-19 symptoms experienced. The findings suggest that young adults who engaged in regular physical activity reported significantly fewer severe symptoms and faster recovery rates compared to their inactive counterparts. This study highlights the potential benefits of maintaining physical activity during pandemics and provides recommendations for public health strategies to incorporate exercise into disease prevention programs.